MALE REPRESENTATION IN SUPER BOWL COMMERCIALS 2019 - Quynh, Vu Thi Phuong (VNU Journal of Foreign Studies, 2023)
Gender, especially female, representation in advertising has been extensively studied in recent decades; however, few studies have looked into male representation in the current media landscape. This article presents a multimodal critical discourse analysis (CDA) study on the contemporary depiction of men in Super Bowl commercials. Focusing on 57 advertisements aired during Super Bowl 2019, the research finds that male representation in TV advertisements is still largely confined by traditional male norms, despite the recent transformation in societal male roles. Besides, the findings also suggest that in negotiation with the rise in female power, male power does not decline, but varies in manifestation. Other findings include the dualistic view in male portrayal, and the normalization of men as the target of jokes. The study serves as an appeal for the reinvention of masculinity in today’s world, and for more visible, creative efforts to challenge traditional male stereotypes in advertising and media.